Behavioral analysis of childbearing age women against IVA screening using health belief model - Yustina Ananti; Fatimah Sari (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2021)
Background: In Indonesia, cervical cancer is the second most common cancer that attacks women of childbearing age. VIA screening (acetic acid visual inspection) is a cervical cancer prevention and control program with the aim of detecting pre-cancerous and cancerous conditions at an early stage. Based on the fact that more than 50% of women diagnosed with cancer have never been screened. Objective: the purpose of this study was to explain the behavior of women of childbearing age towards VIA screening using the health belief model. Methods: the study used a cross sectional approach, conducted from October to December 2019. Data were collected using interview questionnaires, geographic area, occupation, VIA screening, individual knowledge and perception using the Health Belif Model on 160 female respondents of childbearing age in the Puskesmas area. Bantul Regency, Yogyakarta. Descriptive analysis, chi-square logistic regression, univariate, bevariate and multivariate. Results: From 160 respondents, based on geographic area 50% were in cities and plains and 50% in coastal and hilly areas, 55.6% had had IVA screening, 66.9% were unemployed and 53.1% had good knowledge. Perceived susceptibility of being diagnosed with cervical cancer = 0.011<0.05, perceived saverity = 0.023<0.05, perceived thread = 0.015<0.05, perceived benefit = 0.023 <0.05, perceived barriers = 0.030<0 .05 and cues to action = 0.045<0.05 on VIA screening. The Negelkerke R Square test is 0.186 and the effect of the independent variable on the dependent variable is perceived susceptibility = 0.028, perceived benefit = 0.043 and perceived barriers = 0.050. Conclusion: There is a relationship between the behavior of women of childbearing age on VIA screening using the health belief model, namely perceived susceptibility, perceived saverity, perceived thread, perceived benefits, perceived barriers, cues to action with R Square 0.186 and the influential variables are perceived susceptibility, perceived benefit and perceived barriers.